Preferensi Tafsir Nusantara di era Jaringan Mesir dan India: Studi Kasus pada Tafsir Qur’an Karim karya Mahmud Yunus - Muhammad Khoirul Anwar (Ushuluddin Faculty, PTIQ Institute, 2022)
This article aims to conduct an in-depth analysis related to the interest (preference) for references to the interpretation of the archipelago in the era of the Egyptian and Indian networks. The network referred to in this article is the popularity of commentary works from Egypt and India, which were discussed in Indonesia then. This study takes the case of Mahmud Yunus, Tafsir Qur’an Karim by analyzing issues of modernity. Periodically, this interpretation was written in the era of massive modern thought from Egyptian and Indian currents, both of which are evidence of the intertwining of the scientific network of Indonesian scholars with scholars from the two countries. From Egypt emerged Tafsir al-Mannar, written by Muhammad Abduh, and from India, there was the work The Holy Qur’an by Maulana Muhammad Ali, both of which contributed to the interpretation discourse in the archipelago. This article concludes that Mahmud Yunus, in his commentary, is very responsive to issues of modernity which are the trend of discussion in interpretation. Still, in his explanation, he does not mention many academic references, so he does not provide a comprehensive scientific explanation. This style is what differentiates Mahmud Yunus from Tafsir Al-Mannar and The Holy Qur’an even though it appears at the same time. Nevertheless, the author finds Mahmud Yunus blatantly quoting the opinion of Tafsir Al-Mannar for certain themes.